Recent advances on the thermal properties and applications of nanofluids: From nanomedicine to renewable energies. (25th January 2022) - Souza, Reinaldo R.; Gonçalves, Inês M.; Rodrigues, Raquel O.; Minas, Graça; Miranda, J.M.; Moreira, António L.N.; Lima, Rui; Coutinho, Gonçalo; Pereira, J.E.; Moita, Ana S.
Highlights: Most recent applications of nanofluids (NFs), from nanomedicine to renewable energies. There are a large number of parameters that affect the thermal performance of NFs. The superior k of NFs is the main attraction for the majority of the applications. Identification of several challenges and potential solutions to accelerate the NFs translation. Direct visualization devices are promising systems to solve thermal limitations of NFs. Abstract: The nanofluids (NFs) are known as a colloidal suspension where nanoparticles (NPs) are dispersed in conventional base fluids (BFs). This suspension has been frequently used to augment the heat transfer (HT) capacity of a fluid by studying their thermophysical properties. This review outlines the most recent advances on the NFs thermal properties and on their applications that are being used in different fields of engineering, ranging from nanomedicine to renewable energies. In the latter, several relevant advances have been achieved in mobility and propulsion with relevant application in defense and military technologies. Hence, specific applications of NFs in electronics cooling, heat exchangers, heat pipes, solar energy, nanomedicine, space technology, among others, have been reviewed and presented. Overall, the research performed in this subject has shown that several parameters can impact the thermal properties of the NFs including the BF, NPs size, concentration, shape and NPs fabrication procedures. In this review, the most relevant parameters are identified and debated, to provide guidance and inspire researchers to develop low cost NFs with high thermal properties. In addition, the models for predicting the specific heat, viscosity, thermal conductivity and density of NFs are listed and evaluated in a comprehensive way. Based on the results that the literature presents, there are still many models to be validated and explored. Finally, the challenges and several unresolved issues related to NFs flows are discussed and possible solutions are suggested to solve them.